EDUCATION SYSTEM AND ORGANIZATION OF EDUCATION IN THE CASE OF UZBEKISTAN AND FINLAND - Marjona, Abdukholikova (PT. Antis International Publisher, 2024)
this article sheds light on education, educational systems, and the educational system of Uzbekistan and Finland, a unique tool, and what factors need to be paid attention to in the organization of education.